2017
DOI: 10.1002/ptr.5785
|View full text |Cite
|
Sign up to set email alerts
|

Matrine Suppresses the ER-positive MCF Cells by Regulating Energy Metabolism and Endoplasmic Reticulum Stress Signaling Pathway

Abstract: Matrine (C H N O), an alkaloid that is one of the main active components from Sophora flavescens. Matrine has been demonstrated to have therapeutic effects on various solid tumors, including breast cancer, but the mechanism still needs further study. Endoplasmic reticulum (ER)-positive Michigan Cancer Foundation cells were cultured, and matrine was added in various amounts to measure the dose-dependent and time-dependent cytotoxicity. Hoechst 33258 staining was used to observed nuclear morphological changes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Literature has reported that Matrine has anti-apoptotic effect through endoplasmic reticulum pathway and Osthole also has anti-apoptotic effects respectively [18,25,26]. In this study, the synergistic inhibitory effect of Matrine combined with Osthole on PCV2-induced apoptosis was demonstrated and the result was consistent with the conclusion that Matrine and Osthole alone have anti-apoptosis effects.…”
Section: Discussionsupporting
confidence: 88%
“…Literature has reported that Matrine has anti-apoptotic effect through endoplasmic reticulum pathway and Osthole also has anti-apoptotic effects respectively [18,25,26]. In this study, the synergistic inhibitory effect of Matrine combined with Osthole on PCV2-induced apoptosis was demonstrated and the result was consistent with the conclusion that Matrine and Osthole alone have anti-apoptosis effects.…”
Section: Discussionsupporting
confidence: 88%
“…On the one hand, hepatitis B and atherosclerosis are considered to be associated with excessive ER stress, and Mat has a good therapeutic effect on these two diseases [ 45 48 ]. On the other hand, some researchers have discovered that Mat also exerts anti-cancer effects by aggravating ER stress [ 49 ]. The increase of SERCA2 activity was demonstrated in cancer cells and is considered to protect cancer cells from apoptosis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shao et al (2013) reported that matrine can inhibit the proliferation of breast cancer MCF7, BT-474, and MDA-MB-231 cells, which may be related to the inhibition of inhibitory k B kinase b (IKKb) regulation of nuclear factor k B (NF-kB) signaling pathway. Matrine can induce endoplasmic reticulum stress in MCF-7 cells, downregulate the expression of hexokinase II, inhibit energy metabolism, promote apoptosis (Xiao et al, 2017), and reverse the drug resistance of MCF-7/ADR cells. Adriamycin (ADR) accumulates in cells and induces apoptosis in MCF-7/ADR cells by modulating the PI3K/AKT signaling pathway (Zhou B. G. et al, 2018).…”
Section: Lung Cancermentioning
confidence: 99%